Quantifying the Roman economy (Oxford ; New York)
xviii, 356 s.
Keywords: "This book contains a number of chapters on the Roman economy which discuss methods of analysing the performance of the economy of the Mediterranean world under Roman imperial rule in the period c.100 BC to AD 350 through quantification. It focuses on the methods and problems involved in identifying and analyzing the characteristics of economic integration, growth, and decline in this period. In particular, it attempts to suggest how a complex and diverse economic world can be better understood by using quantifiable and proxy data to measure these processes in different parts of the Mediterranean world. The data are drawn from both documentary and archaeological sources, and the book emphasizes the need to draw together different kinds of written and artefactual evidence and to describe the ways in which they complement each other. This approach is pursued in a series of analyses of approaches specific economic sectors: demography, urbanization and settlement patterns, the agrarian economy, patterns of trade and commerce, mining, metal supply, and coinage. The book offers a survey of the opportunities for advancing understanding of the economic and technological development of the Roman empire by using the tools and techniques of economic history and statistical analysis." --